2010
DOI: 10.1063/1.3453871
|View full text |Cite
|
Sign up to set email alerts
|

Photocurrent characteristics of two-dimensional-electron-gas-based AlGaN/GaN metal-semiconductor-metal photodetectors

Abstract: Articles you may be interested inOn the origin of the two-dimensional electron gas at AlGaN/GaN heterojunctions and its influence on recessed-gate metal-insulator-semiconductor high electron mobility transistors J. Appl. Phys. 116, 134506 (2014); 10.1063/1.4896900Performance comparison of front-and back-illuminated AlGaN-based metal-semiconductor-metal solar-blind ultraviolet photodetectors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…At the time, we get the absorbance spectrum line's match value. The optical distance and detection range of the sensor can be adjusted in this application program; for example, when the sensor's optical distance is 1 cm, the detection range of nitrobenzene is 0.05-50 ppm, the detection range for dichlorophen is 0.1-100 ppm, and the detection range for chlorobenzene is 30-3,000 ppm (Chen et al, 2009;Huang et al, 2010;Nanjing University, 2012).…”
Section: Ultraviolet Sensormentioning
confidence: 99%
“…At the time, we get the absorbance spectrum line's match value. The optical distance and detection range of the sensor can be adjusted in this application program; for example, when the sensor's optical distance is 1 cm, the detection range of nitrobenzene is 0.05-50 ppm, the detection range for dichlorophen is 0.1-100 ppm, and the detection range for chlorobenzene is 30-3,000 ppm (Chen et al, 2009;Huang et al, 2010;Nanjing University, 2012).…”
Section: Ultraviolet Sensormentioning
confidence: 99%
“…Such requirement includes the preparation of an AlGaN/GaN heterojunction to obtain a 2D electron gas in a device with high electron mobility transistors. [5][6][7][8] Conversely, graphene, a typical 2D material with broad applications, has attracted wide attention in recent years [9] due to its excellent properties, such as atomic thickness and highelectron mobility. Previous studies have demonstrated that graphene can form heterojunctions with GaN, [10] Ga 2 O 3 , [11,12] and SiC.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [3,4] have linked the increase in 2DEG channel conductance to the change in state of charge at the surface level. Other studies [4,5] have considered the absorption in the GaN buffer layer, but the photo-generated hole transport mechanisms in this region are not explained. In addition, it has been shown that the absorption of UV photons having energy higher than the bandgap of the AlGaN and the resulting gain is due to the generation of "photovoltages" (electron-hole separation) between the surface and the channel and the buffer/substrate interface and the channel [6].…”
Section: Introductionmentioning
confidence: 99%